Surfactant-Free Electrodeposition of Ag Dendrites as Photocatalyst for Methylene Blue Degradation. (November 2019) - Dhanasmoro, Lintang; Budi, Setia
Abstract: Ag dendrites have successfully fabricated through square-wave electrodeposition method. The electrochemical properties of Ag dendrites were examined via electrochemical impedance spectroscopy and cyclic voltammetry techniques in a solution containing 0.5 M KCl. It was found that Ag dendrites demonstrated equivalent series and charge transfer resistance of 91.3 Ω and 473.7 Ω, respectively. The highest specific capacitance value of Ag dendrites obtained 0.98 F/g at scan rate 10 mV/s. The recorded photocatalytic activities towards methylene blue (MB) degradation under UV light irradiation showed that photocatalytic performance of Ag dendrites reaches approximately 41.88%.